La dimension européenne de la libéralisation des terres et les réformes agraires du milieu du 18e siècle au début du 19e - Jessenne, Jean Pierre (2021)
This paper, a summary of current knowledge, aims at showing the widespread aspirations for agrarian reforms in Enlightenment Europe. It goes beyond the compartmentalization of national historiographies and focuses on the intense exchange of ideas and agronomic experiences. The reforms of farm ownership methods are inseparable from reflections on political economy and social organization. The first attempts at reform in the years 1760-1780 gave rise to strong social tensions and divergent reactions from European states. The French Revolution was agitated by strong contradictions, and it resulted in a form of moderate agrarian liberalism. It left its mark on Europe, without imposing a model, it rather contributed to accentuating national differentiations: while some countries carried on their reforms, others embraced a conservative reaction.